Nanoscale imaging of charge carrier transport in water splitting photoanodes - Johanna Eichhorn (Nature Portfolio, 2018)
The performance of energy materials is affected by structural defects, as well as physicochemical heterogeneity over different length scales. Here the authors map nanoscale correlations between morphological and functional heterogeneity, quantifying the trap states limiting electronic transport in bismuth vanadate thin films.